Effects of soil type, salinity and vesicula arbuscular mycorrhiza on growth and foliar elements in mimusops zeyheri (sond.) indigenour fruit trees - Nkuna, Thabo Selby (My University, 2018)
The evergreen Red Milkwood (Mimusops zeyheri Sond.) is being targeted as a rural and urban-greening tree in Limpopo Province, due to its excellent nutritional, pharmaceutical and aesthetic attributes. Slow growth of M. zeyheri seedlings is the main drawback in the potential domestication and commercialisation of this tree species. The objectives of this study were to determine (1) the influence of soil type on root growth and foliar nutrient elements in M. zeyheri seedlings, (2) the degree of salt tolerance in M. zeyheri seedlings and (3) the influence of vesicular arbuscular mycorrhiza (VAM) fungi on growth of M. zeyheri seedlings. Objective 1 was achieved in clay, calcareous, loam and sandy soils. At 60 days after the treatments, soil type effects were significant on plant height, leaf number, chlorophyll content of primary leaves (dicots), chlorophyll content of secondary leaves, root length, number of root branches and dry root mass, contributing 60, 72, 84, 85, 74, 80 and 40% in total treatment variation (TTV) of the respective variables. Objective 2 was achieved by exposing seedlings to 0, 2, 4, 8, 16, 32, 64 and 128 NaCl + CaCl2 mM/m3 at 3:1 ratio. At 90 days after the treatments, salinity effects were significant on leaf number, dry shoot mass, root length and leaf length, contributing 73, 60, 50 and 64% in TTV of the respective variables. Leaf number, dry shoot mass, root length and leaf length each against increasing concentration of salinity exhibited positive curvilinear quadratic relations, with 74, 91, 95 and 66% associations, respectively. Responses of essential nutrient accumulation in leaf tissues of M. zeyheri to salt treatments had significant effects on K and Na, contributing 28 and 19% in TTV of the respective variables. Potassium over increasing salt concentrations exhibited positive quadratic relations and Na over increasing salt concentrations, exhibited negative quadratic relations. The models for each relation were explained by 95 and 86%, respectively. Objective 3 was achieved by exposing seedlings to 0, 10, 20, 30, 40, 50, 60 and 70 g VAM per plant. At 90 days after the treatments, VAM effects were significant on plant height, leaf number, stem diameter and chlorophyll content contributing, 49, 65, 60 and 61% in TTV of the respective variables. Plant height, leaf number and chlorophyll content each against increasing VAM levels exhibited negative quadratic relations, with 97, 83 and 80% associates, respectively. In conclusion, the use of soil type to promote growth and accumulation of essential nutrient elements on M. zeyheri seedlings demonstrated that clay soil could be suitable for cultivation of M. zeyheri. Also chloride salt concentrations included all three phases of density-dependent growth (DDG) patterns, whereas VAM levels used in the study were already in the last two phases of DDG patterns. Vesicular arbuscular mycorrhiza treatment did not have significant effects on Ca, Fe, K, Na and Zn in leaf tissues of M. zeyheri seedlings. In conclusion, soil with high clay content could be ideal when raising M. zeyheri seedlings. However, salt concentration of 8.11 mM/m3 exhibited the stimulation of M. zeyheri seedlings growth, Therefore, lower concentration less than 8.11 mM/m3 shown to be toxic by reducing the plant growth. In contrast, 5.554 g per plant of VAM will supreme for growth and development of M. zeyheri seedlings.
Thesis (M. Agric. (Plant Production)) -- University of Limpopo, 2018
Keywords: Soil type; Salinity; Mycorrhiza; Indigenous fruit trees; Soil science; Salinity; Soils, Salts in